Emotional Labour in Social Workers' Encounters with Children and Their Families. (19th April 2018) - Winter, Karen; Morrison, Fiona; Cree, Viviene; Ruch, Gillian; Hadfield, Mark; Hallett, Sophie
Abstract: The ways in which social workers experience a range of emotions that are evoked in their professional relationships with children and families is an area that is little focused upon and yet the processes involved in their expression and management can have profound implications for all involved. Theoretically informed by sociological concepts and combining data from a two-year, UK four-nation, ESRC-funded research project, 'Talking and Listening to Children' (TLC), this paper explores the ways in which social work organisational contexts and dynamics give rise to 'feeling rules' in the workplace and the impact of these on social workers' relationships with children and families. Using Hochschild's (1983) emotional labour analytical framework, the paper highlights that the management and expression of social workers' feelings are filtered through personal, professional and organisational contexts. The implications of these pervasive and powerful processes are explored. The paper concludes by considering the significant, wide-reaching implications of this focus on the experience, expression and management of emotion for everyday social work practice in both children and families settings specifically and other social work practice contexts more broadly.